Aktualisasi Nilai Bela Negara Mahasiswa Asrama Bela Negara UPN “Veteran” Jawa Timur - Leticia Nuzululita Agustine; Sri Wibawani (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Defending the country is the right, duty, and responsibility of the people to protect and guarantee the sovereignty of the country based on the people's love for life and the country. The form of defending the country that can be carried out by the younger generation is by carrying out the basic values ​​of defending the country which include love of the country, awareness of the nation and state, believing in Pancasila as the state ideology, being willing to make sacrifices and having the initial ability to defend the country so that by having this attitude it will become a person. a nation with national knowledge and love of the homeland. UPN "Veteran" East Java has a dormitory based on national defense to support the process of forming national defense character in its female students. This research aims to measure the actualization of national defense values ​​for students at the UPN "Veteran" East Java State defense dormitory. The method used is descriptive quantitative. Data collection techniques in this research are questionnaires, observation, and documentation. The sample this study 133 students at the UPN "Veteran" East Java State Defense Dormitory. The data analysis techniques for this research are descriptive statistics, factor analysis, reliability testing, and validity testing using SPSS For Windows Release 23. The results of this research are that the 5 national defense values ​​have relatively high category results so they have a big influence on the actualization of students' national defense values. UPN "Veteran" East Java state defense dormitory.